1998
DOI: 10.1002/(sici)1097-4628(19980214)67:7<1301::aid-app21>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

PCL-PEG-PCL triblock ester-ether copolydiol-based waterborne polyurethane. II. Effect of NCO/OH mole ratio and DMPA content on the physical properties

Abstract: This article was focused on the effects of the NCO/OH molar ratio and 2,2-bis(hydroxyl methyl) propionic acid (DMPA) content during prepolymerization on the physical properties of synthesized waterborne polyurethane (WBPU) by using the polycaprolactone-poly(ethyl glycol) -polycaprolactone triblock copolydiol (PCL-PEG-PCL) as the soft segment. The results showed that the particle size of the WBPUs' dispersion decreased with a decreasing NCO/OH molar ratio or increasing DMPA content. Regarding thermal and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 5 publications
1
26
1
Order By: Relevance
“…The particle size is affected by several external and internal factors of which the proportion of ionic centres is the most important. Similar behaviour has been observed for other systems including those based on IPDI17–19 and results from the maintenance of a uniform density of charged groups on the surface. The dispersion particles are stabilised through the presence of the electrical double layer generated by the surface carboxylic groups and their counterions.…”
Section: Resultsmentioning
confidence: 99%
“…The particle size is affected by several external and internal factors of which the proportion of ionic centres is the most important. Similar behaviour has been observed for other systems including those based on IPDI17–19 and results from the maintenance of a uniform density of charged groups on the surface. The dispersion particles are stabilised through the presence of the electrical double layer generated by the surface carboxylic groups and their counterions.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of TPUs depend on many variables, such as the chemical structure of each type of segment, the molecular weight of the soft segments, the hard/soft segment content ratio, etc 1–4. In addition, it is well known that the polymerization method and preparation conditions affect the microstructure and the mechanical properties of TPUs 5–12…”
Section: Introductionmentioning
confidence: 99%
“…Generally, mixed polyols or special type polyols were used to impart special properties to PU. Yen et al6 used polyol blends such as binary [poly(ethylene glycol)/polypropylene glycol (PEG/PPG), PPG/poly(tetramethylene oxide) glycol (PTMG), and PEG/PTMG] or ternary (PEG/PPG/PTMG) systems for waterborne polyurethane (WBPU). They found that the WBPU having different polyol components had significantly different particle sizes and dispersion behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…PDMS/PTMG‐based materials had higher water absorption values than either the pure PTMG or pure PDMS‐based material. Yen et al12, 13 synthesized the polycaprolactone–poly(ethylene glycol)–polycaprolactone (PCL–PEG–PCL) triblock copolydiol from PEG and ϵ‐caprolactone under uncatalyzed reaction conditions according to Piero's synthesis method,14 and examined the effects of length ratios of PEG/PCL chains on the WVP of WBPU‐coated fabrics.…”
Section: Introductionmentioning
confidence: 99%